Preclinical Evidence and Possible Mechanisms of Rhodiola rosea L. and Its Components for Ischemic Stroke: A Systematic Review and Meta-Analysis - Li, Yan; Cai, Miao; Mao, Gen-Xiang; Shu, Qin-Fen; Liu, Xiao-Bei; Liu, Xiao-Li (Frontiers in Pharmacology, 2021)
Background: Rhodiola rosea L. is commonly used for hundreds of years to treat a variety of common conditions and diseases including Alzheimer’s disease, cardiovascular disease, cognitive dysfunctions, cancer, and stroke. Previous studies reported that Rhodiola rosea L. and its components (RRC) improve ischemia stroke in animal models. Here, we conducted a systematic review and meta-analysis for preclinical studies to evaluate the effects of RRC and the probable neuroprotective mechanismson in ischemic stroke. Methods: Studies of RRC on ischemic stroke animal models were searched in 7 databases from inception to June 2020. The primary measured outcomes included the neural functional deficit score (NFS), infarct volume (IV), brain water content, cell viability, apoptotic cells, TUNEL-positive cells, Bcl-2 level and TNF-α level. The secondary outcome measures were possible mechanisms of RRC for ischemic stroke. All the data were analyzed via RevMan version 5.3. Results: 14 studies involving 310 animals were identified. Methodological quality for each included studies was accessed according to the CAMARADES 10-item checklist. The quality score of studies range from 1 to 7, and the median was 5.29. Pooled preclinical data showed that compared with the controls, RRC could improve NFS (Zea Longa (P < 0.01), mNSS (P < 0.01)), IV (P < 0.01), as well as brain edema (P < 0.01). It also can increase cell viability (P < 0.01), Bcl-2 level (P < 0.01) and reduce TNF-α level (P < 0.01), TUNEL-positive cells (P < 0.01), apoptotic cells (P < 0.01). Conclusion: The findings suggested that RRC can improve ischemia stroke. The possible mechanisms of RRC are largely through antioxidant, anti-apoptosis activities, anti-inflammatory, repressing lipid peroxidation, and alleviating the pathological blood brain barrier damage.